Sosialisasi Hukum Bahaya Bullying Bagi Remaja Melalui Media Sosial - Suriani Suriani; M. Hafiz Nurhasan Sihombing; Gusthi Sulistio Al Fath; Deviana Dewi Sirait; Sri Diana; Khairunnisak Panjaitan (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This study aims to conduct legal socialization regarding the dangers of bullying for teenagers through social media at SMA Taman Siswa Sukadamai. Bullying is becoming an increasingly concerning phenomenon among teenagers, especially with the widespread use of social media. This has triggered the expansion of legal socialization efforts to increase awareness of these dangers. The methods used in this community service include counseling, workshops, and the provision of educational materials tailored to social media platforms. The results indicate an improvement in teenagers' understanding of the legal implications of bullying and an enhancement of their abilities to manage conflicts constructively. These steps are crucial in creating a safe school environment and supporting positive adolescent growth. Through effective legal socialization, it is hoped that bullying cases can be reduced and that an inclusive and empathetic school culture can be fostered. In conclusion, efforts to socialize the law regarding the dangers of bullying for teenagers through social media at SMA have a significant positive impact on raising awareness and changing adolescent behaviors related to bullying.